ENVIRONMENTAL PERFORMANCE: THE CONTRIBUTION OF GREEN INTELLECTUAL CAPITAL AND ENVIRONMENTAL AWARENESS OF MANUFACTURING MSME BUSINESS - Farhan Adam; Abdul Kahar; Sugianto; Mustamin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to examine and test the components of Green Intellectual Capital on Environmental Performance by looking at the role of Business Owners' Environmental Awareness in Moderating this relationship in MSMEs located in disaster affected areas of Palu, Sigi and Donggala (PASIGALA18). A quantitative research method was applied by distributing questionnaires to 60 business owners in the manufacturing MSME sector in the PASIGALA18 area and applying Moderated Regression Analysis using SPSS 27. The research findings reveal that the Green Intellectual Capital component contributes to Environmental Performance in the form of Green Human Capital (β1 = 0.604, p-value <0.001); Green Structural Capital (β2 = 0.252, p-value 0.012); and Green Relational Capital (β3 = 0.411, p-value 0.001). Meanwhile, Environmental Awareness shows a high explanatory power of the model. The role of environmental awareness strengthens all contributions of the Green Intellectual Capital component to the Environmental Performance of MSME actors. The findings indicate that investment in green knowledge, systems, and networks supported by increased business owner awareness significantly improves the environmental performance of MSMEs. The research has implications for local government policy recommendations to improve training programs for MSME actors to integrate Green Intellectual Capital and strengthen environmental awareness in achieving sustainable environmentally friendly production practices.